The world food crisis, land degradation, and sustainable land management: Linkages, opportunities, and constraints - Pender, John L. (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2009)
In recent years, world food prices have skyrocketed, causing severe hardship for poor and vulnerable people throughout the world. Between 2005 and 2008, world prices of rice, wheat, and maize more than doubled (Figure S.1); pushing more than 100 million people into poverty, including nearly 30 million people in Africa. Although food prices have declined from the peaks seen in early 2008, they remained well above the levels seen in recent years in early 2009. The causes of the food price crisis include many factors affecting the global supply, demand, and trade of food commodities. Among the most important factors were rising oil prices, leading to increased costs of producing, processing, and transporting food; increased use of food crops for biofuel production; poor harvests in some major producing regions; rapid economic growth in many developing countries; and decades of underinvestment in agricultural research and development.